2017
DOI: 10.1089/cren.2017.0033
|View full text |Cite
|
Sign up to set email alerts
|

A Large Posteriorly Located Prostatic Mass Lesion Challenging the Robotic Surgeon: Prostate Leiomyoma

Abstract: Background: Prostatic leiomyoma is a benign and rare condition of the prostate. Robotic surgery is increasingly being applied in the surgical management of prostate cancer.Case Presentation: Herein, a mass lesion that was located in the posterior part of the prostate between seminal vesicles that was identified during robotic surgery is presented. This lesion further challenged the console surgeon during performing a robotic radical prostatectomy procedure for a 200 g large prostate with prostate cancer.Conclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 5 publications
0
5
0
2
Order By: Relevance
“…After the selection procedure according to PRISMA (Figure 4), a total of 21 studies were included in our systematic review (1,2,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There were 35 cases of leiomyoma of the prostate included for analysis and characteristics of the cases are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…After the selection procedure according to PRISMA (Figure 4), a total of 21 studies were included in our systematic review (1,2,4,(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23). There were 35 cases of leiomyoma of the prostate included for analysis and characteristics of the cases are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…A review of the published literature on leiomyomas identified six [3][4][5][6][7][8], single-patient case reports of elderly (age range: 54-82 years) males diagnosed with a prostatic leiomyoma [3][4][5][6][7][8]. All but one case report have PSA levels reported ( Two of the case reports mentioned the administration of alpha-blockade agents to treat BPH [5,6]. All patients presented with prostamegaly and a presumptive diagnosis of BPH, with the exception of one who had a known biopsy-proven adenocarcinoma [5].…”
Section: Discussionmentioning
confidence: 99%
“…All but one case report have PSA levels reported ( Two of the case reports mentioned the administration of alpha-blockade agents to treat BPH [5,6]. All patients presented with prostamegaly and a presumptive diagnosis of BPH, with the exception of one who had a known biopsy-proven adenocarcinoma [5]. In three reports, patients presented with acute urinary retention and two with gross hematuria [4,6,7].…”
Section: Discussionmentioning
confidence: 99%
“…Nokturi ve dizüri en sık görülen klinik bulgulardır. Serum PSA düzeyi bu olgularda genellikle normaldir; leiomyoma eşlik eden adenokarsinom veya seminal vezikül lokalizasyonlu leiomyom olgularında ise yüksek serum PSA düzeyi gözlemlenebilir (5,6). Olgumuzun yaşı 77 idi ve infravezikal obstrüksiyon semptomları ile kliniğe başvurmuştu; serum PSA düzeyi normaldi.…”
Section: Discussionunclassified
“…Kalın iğne biyopsisi uygulanan prostat leiomyomu olgularında düşük dereceli malignitelerin ekarte edilmesinde zorluk yaşandığı, böylece hastaya radikal prostatektomi ve bölgesel lenf nodu disseksiyonu gibi geniş çaplı cerrahi işlemlerin uygulanabildiği rapor edilmiştir (7). Prostat adenokarsinomu ve leiomyomuna eş zamanlı rastlanılması mümkündür (6). Bu nedenle prostat leiomyomu olgularında leiomyom dışı prostat dokusunun dikkatlice incelenmesi gerekmektedir.…”
Section: Discussionunclassified